Effect of E-Money on Consumptive Behavior of the Batam Community - Candy Candy; Keyi Sylvia Tania; Soveinia Soveinia; Winny Stevania (JPIM (Jurnal Penelitian Ilmu Manajemen), 2022)
Humans have 3 kinds of needs that must be met to survive, namely primary, secondary and tertiary. Apart from basic needs, a person sometimes cannot control himself, resulting in a purchase without a long consideration based on a desire which is called consumptive behavior. This behavior is again supported by technological developments, where e-money is present as an electronic payment tool. E-money that presents features that are easy, convenient and safe so that there is an increase in its use in the community. The purpose of this study was to measure the relationship of e-money users to consumptive behavior in Batam society. There are significant positive relationship between the use of e-money and consumptive behavior of the Batam community.